Accessibility in tourist sites in Spain: Does it really matter when choosing a destination? - Rucci, Ana Clara (2022)
This work aims to analyse and characterise accessibility in tourism —defined as the conditions for people with access needs— and its relationship with tourism performance. Accessibility is a critical concept —to be defined and measured in a rigorous way— that helps shed light on the particularities of the phenomena, considering consumers and producers of tourism. Spain's solid background in accessible tourism portrays the possibility of elaborating different accessible indicators. We propose and identify an exhaustive set of proxy measures for accessibility under the accessible tourism theoretical framework of the tourism travel chain. We also computed an accessibility index using disaggregated data of 152 Spanish tourist sites (National Statistics Institute of Spain), introducing those measures of accessibility as explanatory variables in a model of tourism performance of sun and cultural destinations. Our results show that accessibility seems not to be a determinant in tourist sites' performance. Sun destinations have better tourism performances than cultural ones, having or not accessible conditions. The findings not only reveal the need to improve and consolidate accessible conditions in cultural destinations, but also disseminate and deepen information channels, especially for people with access needs, before choosing a destination.